2005
DOI: 10.1111/j.1475-1313.2005.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractive group differences in accommodation microfluctuations with changing accommodation stimulus

Abstract: The magnitude of the microfluctuations in the EMMs and EOMs may be influenced primarily by accommodation response-induced zonular relaxation effects or to changes in the physical properties of the accommodation plant with increasing accommodation response. The LOMs may have an increased baseline neural blur threshold, which appears to modulate the magnitude of the accommodative microfluctuations for low accommodation levels. At higher accommodation demands, the changes in the physical properties of the accommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
99
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(113 citation statements)
references
References 68 publications
(210 reference statements)
11
99
3
Order By: Relevance
“…This is unsurprising as Day et al 41 have shown that a greater accommodative response results in a larger variability in the response. The present RMS values are high, but within the range shown by Anderson et al 32 which was 0.1 to 0.7 D for a 2-D response amplitude, even in older participants.…”
Section: Discussionmentioning
confidence: 92%
“…This is unsurprising as Day et al 41 have shown that a greater accommodative response results in a larger variability in the response. The present RMS values are high, but within the range shown by Anderson et al 32 which was 0.1 to 0.7 D for a 2-D response amplitude, even in older participants.…”
Section: Discussionmentioning
confidence: 92%
“…They found that the LFC power increases more rapidly with accommodative demand for EMMs and EOMs, in comparison to LOMs, and that the standard deviation of the fluctuations is higher in LOMs (Day et al. 2006). …”
Section: Discussionmentioning
confidence: 99%
“…As a result, it becomes unstable and fluctuates when focusing on an object, and the fluctuation frequency is around a few hertz. These are called accommodative microfluctuations [10,11,[18][19][20][21][22][23][24]. As people with normal vision look at a close object, the activity of the ciliary body is relatively low when compared to viewing a far object.…”
Section: Accommodative Microfluctuationsmentioning
confidence: 99%
“…Accommodative microfluctuations may be affected by the distance of the target [20,[26][27][28], the pupil diameter [24,[29][30][31], the form of the target [32,33], the luminance of the target [11,34,35], the eye's age, astigmatism [36], visual fatigue [12,20,37,38], biomonocular observation of the target [30,37], and artifacts such as cardiopulmonary signals [39][40][41] or other rhythmical physiological systems. Neurological control also affects the LFC's wavelength, and arterial signals correlate highly to the HFC [11,21].…”
Section: Accommodative Microfluctuationsmentioning
confidence: 99%